2005
DOI: 10.1111/j.1524-475x.2005.04025.x
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Decisional Control: Building the Base for Evidence‐Based Nursing Practice

Abstract: Future research needs to focus on the identification of the differences in decisional control by country, in differing cultural and ethnic groups within countries, and in various geographical areas of countries. The relationship of patient characteristics (e.g., age, gender, education, and income) to decisional control preferences is not clearly identified. A large gap in the research relates to how nurses can facilitate preferred decisional control to improve patient outcomes through evidence-based nursing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“… who found that patients held different views of preferred level of participation and that nurses failed to assess individual patient preferences, paying lip service to patient preferences but not actually involving the patients in decision‐making according to the patient's own perceptions. In this sense, decisional control refers to a hypothetical power struggle where healthcare providers in their traditional roles may believe that they know what is best for patients and so seek to retain total decisional control . However, patients from differing backgrounds, having different resources and capabilities, should be capable of having an impact on participation, communication and decision‐making .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… who found that patients held different views of preferred level of participation and that nurses failed to assess individual patient preferences, paying lip service to patient preferences but not actually involving the patients in decision‐making according to the patient's own perceptions. In this sense, decisional control refers to a hypothetical power struggle where healthcare providers in their traditional roles may believe that they know what is best for patients and so seek to retain total decisional control . However, patients from differing backgrounds, having different resources and capabilities, should be capable of having an impact on participation, communication and decision‐making .…”
Section: Discussionmentioning
confidence: 99%
“…This scale included the assessment of knowledge delivery, the possibility to express wishes and opinions, plus having a say and participating in decision‐making with regards to daily nursing care. However, specific tools measuring decisional control have been created and could have been used together with the ICS‐B‐Decisional control. The ICS‐B‐Decisional control could also be further developed to focus on specific areas of care.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between exhibited participation and preference is important because some people may not have the appropriate information, skills, or support to feel they can participate in a knowledgeable way. 21,[36][37][38][39][40][41] The self-perception of inadequate skills may lead to a stated preference for lower participation in decision making. 19 Another study has taken a similar approach to distinguish preference from behavior in elderly adults.…”
Section: Level Of Participation Clarified As a Behavioral Conceptmentioning
confidence: 99%
“…Decisional control is defined as “an individual’s expectation of having the power to participate in decisions in order to obtain desirable consequences.” 1 Understanding decisional control preferences of patients with advanced cancer regarding cancer care is important as it improves patient–clinician communication, quality cancer care, and patient satisfaction and reduces cost of care. 2–8 Prior studies suggest better patient satisfaction and quality cancer care outcomes when the decisions are patient-centered and shared.…”
Section: Introductionmentioning
confidence: 99%